Numerical analysis on dynamic response and damage threshold characterization of deep rock mass under blasting excavation - Zong, Qi; Lv, Nao; Wang, Haibo; Duan, Jichao (Frontiers in Materials, 2024)
The excessive destruction of surrounding rock in deep tunnel will change the original environmental state and destroy the natural ecological balance. Research on the dynamic response characteristics and damage thresholds of rock masses in deep environments plays a crucial role in determining the excavation range of blasted rock and establishing safety construction scheme. This study employs numerical simulation techniques to investigate the dynamic response characteristics of surrounding rock under different ground stress conditions. By introducing the dynamic ultimate tensile strength criterion, critical fracture stress threshold, and maximum damage radius of rock under coupled dynamic-static loading conditions are determined. The research shows that under uniaxial ground stress condition, increasing ground stress inhibits damage to the surrounding rock and the extension of cracks in the excavation area, while imposing restrictions on the attenuation rate of explosive stress. Under bidirectional equal ground stress condition, an increase in lateral pressure coefficient inhibits the development of damage zones along the excavation contour, yet enhances the extension of cracks in the maximum principal stress direction. Moreover, when lateral pressure coefficient becomes excessively large, the attenuation rate of explosive stress significantly increases. Based on the threshold values of peak particle velocity (PPV), the functional relationship is established to predict safety criteria for deep blasting excavation.